Additive manufacturing and mechanical characterization of high density fully stabilized zirconia. Issue 8 (1st June 2017) - Ghazanfari, Amir; Li, Wenbin; Leu, Ming C.; Watts, Jeremy L.; Hilmas, Gregory E.
Abstract: Mechanical properties of additively manufactured 8 mol% yttria-stabilized zirconia (8YSZ) parts were extensively studied for the first time. A novel freeform extrusion fabrication process, called Ceramic On-Demand Extrusion (CODE), was employed to deposit an aqueous viscous suspension (~50 vol% solids loading) of fully stabilized zirconia powder in a layer-by-layer fashion. Each layer was exposed to infrared radiation after deposition to attain partial solidification due to drying. Before exposure, the layer was surrounded by oil to preclude non-uniform evaporation, which could cause warpage and crack formation. After the fabrication process was completed, the parts were humid-dried in an environmental chamber and densified by sintering under atmospheric pressure. Standard test methods were employed to examine the properties of sintered parts including density, Vickers hardness, fracture toughness, Young's modulus, and flexural strength. Microstructural evaluation was also performed to observe the microstructural morphology and measure grain size. The results indicate that the properties of 8YSZ parts produced by the CODE process match those obtained by conventional fabrication techniques.